Communication Transparency in School Management and Teachers’ Organizational Trust in a University in Beijing, China - Zuo, Xueyuan (Pacific International Journal, 2025)
Effective communication within school management has a significant impact on organizational trust among teachers. Transparency in communication involves openly sharing accurate and timely information, fostering an environment of mutual respect and collaboration. In schools, where teamwork and mutual understanding are crucial, the role of transparent communication cannot be overstated. Recent research has highlighted its profound impact on the development of trust in educational institutions (Rajapaksha & Dissanayake, 2021; Praphatsorn & Wannapiroon, 2023). Transparency in communication can reduce ambiguity and ensure that teachers understand decisions that affect their work, thereby building trust. Transparent communication within school management enables teachers to align their professional goals with those of the institution. This alignment, in turn, fosters a sense of shared responsibility and ownership, strengthening trust in leadership. These practices include regular staff meetings, open lines of communication, and clearly communicated policies. Perceptions of decision fairness are also closely linked to transparency in communication. When school leaders openly share the rationale behind decisions, teachers perceive a greater sense of fairness and inclusion. A study by Ahmad and Farooq i (2021) found that teachers’ trust and morale levels increased significantly in schools that implemented transparent decision-making processes. This trust fostered a supportive environment conducive to collaboration and innovation in teaching practices.